Recent Developments in Linear Interaction Energy Based Binding Free Energy Calculations - Rifai, Eko Aditya; van Dijk, Marc; Geerke, Daan P. (Frontiers in Molecular Biosciences, 2020)
The linear interaction energy (LIE) approach is an end-point method to compute binding affinities. As such it combines explicit conformational sampling (of the protein-bound and unbound-ligand states) with efficiency in calculating values for the protein-ligand binding free energy DGbind. This perspective summarizes our recent efforts to use molecular simulation and empirically calibrated LIE models for accurate and efficient calculation of DGbind for diverse sets of compounds binding to flexible proteins (e.g. Cytochrome P450s and other proteins of direct pharmaceutical or biochemical interest). Such proteins pose challenges on DGbind computation, which we tackle using a previously introduced statistically weighted LIE scheme. Because calibrated LIE models require empirical fitting of scaling parameters, they need to be accompanied with an applicability domain (AD) definition to provide a measure of confidence for predictions for arbitrary query compounds within a reference frame defined by a collective chemical and interaction space. To enable AD assessment of LIE predictions (or other protein-structure and -dynamic based DGbind calculations) we recently introduced strategies for AD assignment of LIE models, based on simulation and training data only. These strategies are reviewed here as well, together with available tools to facilitate and/or automate LIE computation (including software for combined statistically-weighted LIE calculations and AD assessment).